Manufacturing Technique of an Impression Compound Applicator Gun - Frederico Santos Lages; Lia Silva de Castilho; Danilo Rocha Dias; Ênio Lacerda Vilaça (Association of Support to Oral Health Research (APESB), 2024)
Objective: To describe a practical way of applying impression compound in stick form using a safe electrical instrument. Material and Methods:Impression compound is a thermoplastic, rigid, reversible molding material in dentistry that requires a temperature of 55-60 °C for plasticization. Take a hot-glue gun for 7 mm tubes, which is the same dimension as the stick of impression compound. The gun nozzle has to be enlarged with a drilling machine and a drill to work to a suitable diameter with the impression compound according to the operator's preference. A temperature controller needs to be installed to release the compound in a consistency and temperature suitable for use. If the dentist wants to know the exact temperature of 55-60 °C, they can use an infrared thermometer to measure the position of the regulator on the gun's nozzle. Conclusion: Impression compound continues to be widely used for specific procedures, including impressions in severely resorbed ridges and maxillofacial prostheses, which can benefit from the manufacture of the device described.